2019
DOI: 10.1126/science.aat9689
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular antibiotic visualization reveals a dynamic drug reservoir in infected macrophages

Abstract: Tuberculosis, caused by the intracellular pathogen Mycobacterium tuberculosis, remains the world's deadliest infectious disease. Sterilising chemotherapy requires at least six months of multidrug therapy. Difficulty visualising the subcellular localisation of antibiotics in infected host cells means that it is unclear whether antibiotics penetrate into all mycobacteria-containing compartments in the cell. Here, we combine correlated light, electron and ion microscopy to image the distribution of Bedaquiline in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
142
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(148 citation statements)
references
References 33 publications
5
142
1
Order By: Relevance
“…LC-MS begins with the extraction of lipids from plasma. The most popular method is liquid-liquid extraction using a mixture of dichloromethane/methanol or butanol/methanol [7][8][9]. Methanol destroys and precipitates lipoproteins, and dichloromethane guarantees the effective extraction of a wide range of lipid species from the precipitated lipoproteins.…”
Section: Liquid Chromatography (Lc)-based Techniquesmentioning
confidence: 99%
“…LC-MS begins with the extraction of lipids from plasma. The most popular method is liquid-liquid extraction using a mixture of dichloromethane/methanol or butanol/methanol [7][8][9]. Methanol destroys and precipitates lipoproteins, and dichloromethane guarantees the effective extraction of a wide range of lipid species from the precipitated lipoproteins.…”
Section: Liquid Chromatography (Lc)-based Techniquesmentioning
confidence: 99%
“…These phospholipids may thus be involved in the increase of autophagy and mycobacterial phagosome-lysosome fusion upon BDQ treatment. Consistent with this hypothesis, recent work has shown that BDQ accumulates in host cell lipid droplets and is transferred to MTB as the droplets are consumed by the bacteria, enhancing MTB killing (Greenwood et al, 2019).…”
Section: Discussionmentioning
confidence: 79%
“…Interestingly, it has been proposed that targeting host lipid droplets in foamy macrophages may enhance efficacy of anti-TB agents. The lipophilic antibiotics stored in lipid droplets would be transferred to the intracellular pathogen as M. tuberculosis consumes host lipid droplets as a carbon source for growth [16].…”
Section: Preferable Characteristics Of Targets and Enzyme Inhibitors/mentioning
confidence: 99%